Digital Transformation in School Administration and the Implementation of School Management Information Systems at Madrasah Aliyah Negeri 1 Mataram - Baiq Trisni Yuliantari; Mohamad Mustari; Syarifuddin Syarifuddin (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Digital transformation has become a primary demand in improving the quality of educational governance in the modern era. This study aims to analyze the management of digital transformation in school administration at MAN 1 Mataram, focusing on the implementation process of the School Management Information System (SIMS), the benefits gained, and the challenges encountered. The research employed a qualitative descriptive method with a case study design, involving the principal, teachers, and administrative staff as research subjects. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that MAN 1 Mataram possesses strong digital infrastructure readiness, supported by adequate ICT facilities and competent human resources. The implementation of SIMS has improved administrative efficiency and data transparency; however, it still faces challenges such as power outages, limited internet quotas, and network disruptions. The study concludes that the success of digital transformation depends on infrastructure readiness, digital literacy, and policy support. The implication is that digitalizing school administration can strengthen governance and enhance the effectiveness of educational services. It is recommended that schools and the government continue to improve infrastructure stability, provide digital training, and offer ongoing support for digital-based madrasahs.